Karakterisasi Morfologi 18 Galur Harapan Mentimun Hibrida Tipe Rujak (Cucumis sativus L.) - Mawadatusifa, Mawadatusifa; Farmia, Asih; Aziza, Elea Nur (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
The study aims to determine the characteristics of 18 promising cucumber plant lines to determine the best candidates in 18 promising cucumber plant lines. This study was conducted from August 2024 to May 2025 at CV Ever Fresh Land located in Kediri, East Java. This study used a Non-Factorial Randomized Block Design by comparing 18 internal hybrid promising lines, each of which was evaluated using the hybrid varieties Cordova F1, Batara F1 and Zatavy F1 as controls. This study was conducted with a morphological characteristic study approach based on qualitative characters. Qualitative data were analyzed descriptively. The results showed that there were the best promising line candidates selected based on characteristic analysis through qualitative character observations. The best candidate selected based on these criteria was the promising line 5480. The promising line 5480 has the advantage of qualitative character of dark green fruit color, namely Dark Green (RHS 137 A) and a sweet/not bitter taste